Developing a Problem-Based Student Worksheet Integrated with Scientific Literacy in Thermochemistry - Maria Angelina Barus; Jamalum Purba (Universitas Negeri Medan, 2025)
The purpose of this study was to determine the feasibility and student response to the development of a Problem-Based Integrated Science Literacy Student Worksheet (LKPD) for Thermochemistry. The study used Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). Purposive sampling was used to select 35 students from class XI IPA 1 of SMA Negeri 1 Bangun Purba as the experimental class. The instruments used were a BSNP-based feasibility assessment sheet and a student response questionnaire. The results showed that the developed LKPD was valid and highly suitable for use. This was demonstrated by the average feasibility score of 3.62. The results of the student response questionnaire showed an average score of 3.65, indicating a high level of student interest. It can be concluded that the development of a Problem-Based Integrated Science Literacy Student Worksheet (LKPD) integrated with science literacy is highly effective as a supplementary teaching material in schools because it can improve students' critical thinking skills and motivation to learn thermochemistry.